Contrastive Analysis Between Arabic and Indonesian Badi' Styles/ التحليل التقابلي بين الأساليب البديعية العربية والإندونيسية - Hafidz, Muhammad; Hadi, Nur (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Contrastive analysis is valuable in second language teaching due to certain assumptions: learning difficulties are wholly or partially caused by differences between the mother tongue and the foreign language; the more significant the difference between the first language and the second language, the more pronounced the learning difficulties become; the results of the comparison between the first language and the second language are necessary to anticipate the problems and errors that may arise when learning a foreign language. This study aims to uncover the process and steps of contrastive analysis between Badi' science materials and the Indonesian language style. In this study, it yields Contrastive Analysis Steps: first, description—this step involves two stages, namely explaining the definition of Badi' science materials and elucidating the themes of language styles and their characteristics; second, clarifying the similarities and differences between Badi' science materials and Indonesian language styles; third, predicting difficulties. The author employs Clifford Prator's theory to predict or anticipate the challenges of learning Badi'.